The Internet Knows More Than My Physician: Qualitative Interview Study of People With Rare Diseases and How They Use Online Support Groups - Sadaf Ashtari; Adam Daniel Taylor (JMIR Publications, 2022)
BackgroundPatients struggling with rare diseases may face challenges caused by care providers being unfamiliar with their condition. The life span of people with rare diseases may be the same as that of healthy people, but their quality of life is different. Patients with chronic pain are constantly looking for ways to mitigate their pain. Pain killers are not a permanent solution. In addition to the medical and nonmedical costs of rare diseases for both patients and health care providers, there is a need for sustainable sources of information that are available to help with pain and improve their quality of life, with the goal of reducing physician visits and hospital admissions. ObjectiveThis study investigated the challenges that patients with genetic disorders face in managing their health conditions and finding disease-related information as well as the effect of online peer support groups on pain mitigation and care management. MethodsInterviews were conducted via Zoom between July 2021 and December 2021. Eligible participants were those who were aged >18 years, had a medical diagnosis of any type of Ehlers-Danlos syndrome (EDS) with chronic pain, and were members of any support group. Participants were recruited through an announcement in the research and survey section of The Ehlers-Danlos Syndrome Society web page. Interviews were analyzed using the framework approach. Data were systematically searched to identify patterns, analyze them, and identify themes. Interview audio files were transcribed and independently coded by two researchers (SA and AT). Through an iterative process, a final coding table was agreed upon by the researchers and used to thematically analyze the data. ResultsWe interviewed 30 participants (mean age 37.7, SD 15 years; n=28, 93% were women; n=23, 77% were residing in the United States). Thematic analysis revealed that participants (patients with EDS) were constantly in pain and most of them have not received accurate and timely diagnoses for many years. They expressed their challenges with health care providers regarding diagnosis and treatment, and complained about their providers' lack of support and knowledge. Participants' main sources of information were web-based searches, academic journals, The Ehlers-Danlos Syndrome Society web page, and online peer support groups on Facebook, Reddit, Twitter, and Instagram. Although pain killers, cannabis, and opioids are providing some pain relief, most patients (28/30, 93%) focused on nonmedical approaches, such as hot or ice packs, physical therapy, exercises, massage, mindfulness, and meditation. ConclusionsThis study highlights the information gap between health care providers and patients with genetic disorders. Patients with EDS seek access to information from different web-based sources. To meet the needs of patients with genetic disorders, future interventions via web-based resources for improving the quality of care must be considered by health care professionals and government agencies.